NCOG-02. LONGITUDINAL AND PROSPECTIVE NEUROBEHAVIORAL OUTCOMES IN NEWLY-DIAGNOSED PRIMARY CNS LYMPHOMA PATIENTS TREATED WITH PRIMARY CRANIAL RADIOTHERAPY COMBINED WITH OR WITHOUT MTX-BASED CHEMOTHERAPY. (5th November 2018) - Lin, Shinn-Yn; Yang, Chi-Cheng; Pai, Ping-Ching; Lu, Yu-Jen; Huang, Yin-Cheng; Chuang, Chi-Cheng
Abstract: BACKGROUND: Primary central nervous system lymphoma (PCNSL) is an uncommon disease. Conventional treatment has consisted of either whole-brain radiotherapy (WBRT) or methotrexate (MTX)-based combined modality therapy combining chemotherapy and cranial irradiation. The addition of chemotherapy to cranial RT has significantly improved survival outcomes. However, delayed treatment-related cognitive sequelae have emerged as a significant debilitating complication of combined modality treatment in PCNSL patients, especially when effective treatment can result in disease control and greater survival. Furthermore, the specific contribution of the disease per se and various treatment modalities to cognitive impairment remains unclear because it is difficult to differentiate the individual neurotoxic effects of combined modalities when each can lead to cognitive dysfunctions respectively. Methods: A prospective observational cohort study with longitudinal assessments of neurobehavioral functions, neuroimaging, and activities of daily living in newly-diagnosed PCNSL patients was undertaken at our institute. Neurobehavioral outcomes were integrated into this prospective study and a battery of neuropsychological measures was used to evaluate neurocognitive functions (NCFs). The battery is composed of ten standardized NCF tests, representing four domains sensitive to disease and treatment effects (executive function, attention, verbal memory, psychomotor speed), and activities of daily living. RESULTS: Totally 15 patients with newly-diagnosed PCNSL including two cases with primary intraocular lymphoma were consecutively enrolled from February 2014 to January 2018. Comparing the differences in NCF scores between the baseline and post-treatment intervals, neurobehavioral outcomes consistently remained improving or in almost every domain evaluated in this study. Specifically, the scores of executive functions based on Paced Auditory Serial Addition Test (PACT) significantly improved between the baseline and post-chemoradiation assessment (Wilcoxon rank sum test, p = 0.016). CONCLUSIONS: Under the multidisciplinary treatment guidelines implemented at our institute, both improving neurobehavioral outcomes and maintaining oncological outcomes can be achieved.